Digital screen time usage, prevalence of excessive digital screen time, and its association with mental health, sleep quality, and academic performance among Southern University students - Kaewpradit, Kamollada; Ngamchaliew, Pitchayanont; Buathong, Napakkawat (Frontiers in Psychiatry, 2025)
BackgroundExcessive digital screen time (EDST), which is defined as screen use that surpasses recommended limits, has been found to have detrimental effects on students’ mental health and academic performance. However, there is a paucity of studies investigating EDST in university students in Thailand.ObjectiveTo investigate the prevalence, characteristics, and associations of excessive digital screen time with students’ mental health, sleep quality, and academic performance.MethodsA cross-sectional study was conducted at Southern University, Thailand, between December 2023 and January 2024. A total of 446 students completed self-administered questionnaires assessing DST characteristics, mental health, sleep quality, and academic performance. The tools used included the Depression Anxiety Stress Scale, Rosenberg Self-Esteem Scale, UCLA Loneliness Scale, and Pittsburgh Sleep Quality Index. DST was analyzed by device type and average weekly usage hours, focusing on smartphones, tablets, and computers. EDST was defined as daily usage exceeding 8 hours for smartphones, 6 hours for tablets, or 5 hours for computers. Participants exceeding these thresholds on any device were classified as having EDST. Sampling was conducted using quota sampling across faculties. Data were analyzed using chi-square tests, rank sum tests, and logistic regression, with significance set at P<0.05.ResultsStudents’ median age was 20 years (67.9% women). Most participants used smartphones for 4–6 hours daily (29.7%), tablets for <4 hours (29.8%), and computers for <4 hours (62.6%). Smartphones were primarily used for social media (73.1%), while tablets (28.4%) and computers (19.3%) were used for educational purposes. The prevalence of EDST was 48.4%, including 29.4% on tablets, 22.9% on smartphones, and 7.6% on computers. EDST was significantly associated with younger age (AOR 0.79; 95% CI 0.66–0.94) and enrollment in health science faculties (AOR 1.7; 95% CI 1.01–2.86).ConclusionA high prevalence of EDST was observed among university students, particularly on smartphones and tablets. Younger students and those in health science programs were more prone to EDST, potentially due to higher academic demands and social media use. Interventions to enhance self-awareness, regulate screen time, and develop time management skills are recommended to mitigate its negative effects on mental health and academic performance.